Menumbuhkan Sikap Karakteristik Islam dalam Dunia Pendidikan Pesantren Maupun di Luar Pendidikan Pesantren di Indonesia - Indah Fitriya; Alaika M. Bagus Kurnia PS (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2020)
This research aims to develop the characteristics of students towards islamic education. In Indonesia itself, there are many students who do not have good attitude or character. In this case, of course the role of parents, teachers or ustadz ustadzah and the surrounding environment is very influential. The need for this kind of education is so that Indonesian students become students who are superior to the previous ummah. In this point, teachers or ustadz ustadzah is very the main point, because almost all student time is spent in the sekloahnya, This is true since many schools are implementing a full day system, especially for students who are mondok certainly less likely to meet or meet with both parents. In the Qur'an and al-Hadith, Allah has upheld the attitude of character or morality. Therefore we as ummahnya must apply it. In this case all methods either for school or pesantren are considered to be enough to help foster character attitudes, especially for the school, parents must also take part in shaping their child's character to be good. In 2014, the islamic state 100,000 people were killed in the attack. Seeing this Indonesia should not be afraid anymore to prepare generai rahmatal lil'alamin and in accordance with the ideology of pancasila.